在第问题1中,进一步假设随机变量X的分布函数为[img=36x25]1802f9c520f2a16.png[/img],那么[img=49x25]1802f9c5298f19f.png[/img]的值为( )
A: 0.25
B: 0.5
C: 0
D: 1
A: 0.25
B: 0.5
C: 0
D: 1
举一反三
- 在第问题1中,进一步假设随机变量X的分布函数为[img=36x25]1803215b5d30cbf.png[/img],那么[img=49x25]1803215b66a8f87.png[/img]的值为( ) A: 0.25 B: 0.5 C: 0 D: 1
- 在第问题1中,进一步假设随机变量X的分布函数为[img=36x25]180320b2e391a17.png[/img],那么[img=49x25]180320b2ebf1a9f.png[/img]的值为( ) A: 0.25 B: 0.5 C: 0 D: 1
- 在第问题1中,进一步假设随机变量X的分布函数为[img=36x25]18039520c5ef37d.png[/img],那么[img=49x25]18039520cf51935.png[/img]的值为( ) A: 0.25 B: 0.5 C: 0 D: 1
- 在第问题1中,进一步假设随机变量X的分布函数为[img=36x25]180320b3bf7241b.png[/img],那么[img=49x25]180320b3c713d27.png[/img]的值为( ) A: 0.25 B: 0.5 C: 0 D: 1
- 设随机变量[img=93x25]180327943b4d5c6.png[/img],分布函数为F(x),密度函数为f(x),则有( ) A: P(X<0)=P(X>0) B: f(x)=f(-x) C: P(X<1)=P(X>1) D: F(x)=F(-x)